Effectiveness of financial incentives to improve adherence to maintenance treatment with antipsychotics: cluster randomised controlled trial. - Priebe, S; Yeeles, K; Bremner, S; Lauber, C; Eldridge, S; Ashby, D; David, A; O'Connell, N; Forrest, A; Burns, T (2013)
OBJECTIVE: To test whether offering financial incentives to patients with psychotic disorders is effective in improving adherence to maintenance treatment with antipsychotics. DESIGN: Cluster randomised controlled trial. SETTING: Community mental health teams in secondary psychiatric care in the United Kingdom. PARTICIPANTS: Patients with a diagnosis of schizophrenia, schizoaffective disorder, or bipolar disorder, who were prescribed long acting antipsychotic (depot) injections but had received 75% or less of the prescribed injections. We randomly allocated 73 teams with a total of 141 patients. Primary outcome data were available for 35 intervention teams with 75 patients (96% of randomised) and for 31 control teams with 56 patients (89% of randomised). INTERVENTIONS: Participants in the intervention group were offered £15 (€17; $22) for each depot injection over a 12 month period. Participants in the control condition received treatment as usual. MAIN OUTCOME MEASURE: The primary outcome was the percentage of prescribed depot injections given during the 12 month intervention period. RESULTS: 73 teams with 141 consenting patients were randomised, and outcomes were assessed for 131 patients (93%). Average baseline adherence was 69% in the intervention group and 67% in the control group. During the 12 month trial period adherence was 85% in the intervention group and 71% in the control group. The adjusted effect estimate was 11.5% (95% confidence interval 3.9% to 19.0%, P=0.003). A secondary outcome was an adherence of ≥ 95%, which was achieved in 28% of the intervention group and 5% of the control group (adjusted odds ratio 8.21, 95% confidence interval 2.00 to 33.67, P=0.003). Although differences in clinician rated clinical improvement between the groups failed to reach statistical significance, patients in the intervention group had more favourable subjective quality of life ratings (β=0.71, 95% confidence interval 0.26 to 1.15, P=0.002). The number of admissions to hospital and adverse events were low in both groups and did not show substantial differences. CONCLUSION: Offering modest financial incentives to patients with psychotic disorders is an effective method for improving adherence to maintenance treatment with antipsychotics. TRIAL REGISTRATION: Current Controlled Trials ISRCTN77769281.